Senses and Sensibilities: Stabilising and Changing Tastes in Cross-National Couples. (1st October 2016) - Darmon, Isabelle; Warde, Alan
Abstract: This article examines changes in tastes and practice in the context of establishing and maintaining a new cross-national couple relationship. Interviews provided accounts of the experience of change among fourteen Anglo-French couples. We describe two processes of change which, because accentuated in cross-national couples, reveal mechanisms lying behind the transformation and stabilisation of tastes and diets. Explanation of the evolution of taste and diet can be found in the interplay between aesthetic and ethical drives, incorporated bodily practices and social mechanisms of legitimation and integration. To make sense of gustatory and dietary change, tastes are best understood through their insertion in meaningful sequences, patterns and series.